2010
DOI: 10.1007/s00216-010-4034-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimation of riluzole in human plasma by LC-ESI-MS/MS and its application to a bioequivalence study

Abstract: A novel simple, sensitive, selective, and rapid high-performance liquid chromatography coupled with tandem mass spectrometry method was developed and validated for quantification of riluzole in human plasma. The chromatography was performed by using a Zorbax-SB-C18 (4.6 x 75 mm, 3.5 microm) column , isocratic mobile phase 0.1% formic acid/acetonitrile (10:90 v/v), and an isotope-labeled internal standard (IS), [(13)C,(15)N(2)]riluzole. The extraction of drug and internal standard was performed by liquid-liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…This supposition was verified in vivo , measuring CMAPs elicited by nerve stimulation in ALS patients, to determine the efficiency of neuromuscular transmission. In agreement with our hypothesis, muscle response to nerve stimulation was not influenced by 1 week suspension of riluzole treatment, which produces complete washout of plasma riluzole (Le Liboux et al 1999; Chandu et al 2010). Furthermore, the absence of effects on CMAPs evoked by repetitive nerve stimulation suggests that clinical use of riluzole does not affect the safety factor at the neuromuscular junction in treated patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This supposition was verified in vivo , measuring CMAPs elicited by nerve stimulation in ALS patients, to determine the efficiency of neuromuscular transmission. In agreement with our hypothesis, muscle response to nerve stimulation was not influenced by 1 week suspension of riluzole treatment, which produces complete washout of plasma riluzole (Le Liboux et al 1999; Chandu et al 2010). Furthermore, the absence of effects on CMAPs evoked by repetitive nerve stimulation suggests that clinical use of riluzole does not affect the safety factor at the neuromuscular junction in treated patients.…”
Section: Discussionsupporting
confidence: 90%
“…To examine if riluzole as used in clinical practice affects neuromuscular transmission, we examined 36 ALS patients, measuring the amplitude of compound muscle action potentials (CMAPs) elicited by repetitive nerve stimulation (RNS), which provides a sensitive and non‐invasive assay of neuromuscular transmission. Patients were tested immediately before and after 1 week suspension of riluzole treatment, a time that allows for adequate riluzole washout, which has been estimated at about 40 h (Le Liboux et al 1999; Chandu et al 2010). The test was performed on two different nerve‐muscle groups.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, only one liquid chromatography tandem mass spectrometric (LC-MS/MS) method has been reported for the determination of riluzole in human plasma. Chandu et al, (2010) 12 reported an LC-MS/MS method with a plasma concentration range of 0.5-500 ng mL À1 . This method employs liquidliquid (L-L) extraction, evaporation, drying and reconstitution for sample preparation; however, not sensitive enough for the determination of riluzole concentrations for pharmacokinetic/ bioequivalence studies because of its higher LLOQ.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported for the determination of riluzole in a variety of matrices, such as rat brain (6) mouse plasma (7) and human plasma or serum (8). These methods were performed by using liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS-MS) (9) and spectrophotometry (10). Moreover, several methods of analysis have been reported for the determination of riluzole in bulk, dosage tablet formulations and human serum by spectrophotometric techniques (11), electrochemical and voltammetric analyses (12), densitometric analyses (13) and stability-indicating high-performance liquid chromatography (HPLC) methods (14,15).…”
Section: Introductionmentioning
confidence: 99%